PROFIL PASIEN KONTRAKTUR YANG MENJALANI PERAWATAN LUKA BAKAR DI RSUD ARIFIN ACHMAD PERIODE JANUARI 2011 – DESEMBER 2013 - Rezky Darmawan Hatta; Kuswan Ambar Pamungkas; Dimas P. Nugraha (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACKThe aim of this research is to find out the profile of contracture patients after burn injury treatments. We hold the research at Surgery department, Arifin Achmad hospital from 30th November – 17th December, 2014.This research is descriptive study with cross sectional approach. From 237 populations, we took 12 for our sample with total sampling method. Data collected by the review of medical records of patients hospitalized for burn injury from January 2011 – December 2013. Parameter investigated include patients’ frequent, data for extent of burn injury degree, age, and sex gender were tabulated, computerized and analyzed.From the data we have gathered, we got burn injury patients were 237 people, and 12 patients were contracture. Number of contracture patients mostly in range 15 – 24 years old (33,4%). Number of contracture patients in female patient were 6 people (50%) and in male patients were 6 people (50%). Almost all burn extent was deep dermal (2nd degree) (58,3%) and full thickness (3rd degree) (41,7%).Key word: Burn injury, contracture